Cybersecurity in the Republic of Moldova in the Context of European Integration - Ana-Maria Costea; Natalia Putină; Mircea Brie (Romanian Journal of European Affairs)
The current technological development has brought new opportunities, by reducing the time and transactional costs for several services. Thus, it has increased efficiency in various domains. Yet, at the same time, it has generated new threats and risks that countries need to face in the cyberspace. The unique character of this domain resides in the heterogeneity and multitude of the actors involved. This explains why there are unlimited possibilities for attacks, countless reasons for the attacks to happen, and endless strategies, which make a defence-based strategy futile, if not included within a larger resilience-based perspective. The conception of the state as the sole provider of services for the society no longer stands, as civil society and private actors gradually assume more responsibilities and competences, especially when dealing with the cybersecurity literacy of citizens. This aspect is key since we cannot truly discuss the resilience of a state – and tackle, ipso facto, its security – without taking into consideration the security of its citizens. In order to be protected against cyber threats, citizens need to identify them and find ways to address them. Thus, an adequate knowledge level is fundamental. The present article analyses the way in which the Republic of Moldova, an EU candidate state, is adhering to European norms and values regarding cyber resilience to cope with its cybersecurity threats. Firstly, we examine how its National Cybersecurity Strategy observes the European framework in terms of the state’s and civil society’s involvement in ensuring the security of the Republic of Moldova and of its citizens through awareness raising activities. Since one of the strategy’s objectives is the cooperation with the civil society to increase the citizens’ awareness of cyber threats, this research used a questionnaire designed to assess the Moldovan students’ current level of knowledge of the cyber landscape and of the relevant European norms in this field. The questionnaire also aims to analyse if and how the Moldovan citizens benefited from the different measures taken by the state, the civil society, or other private actors to address this issue.